Scanning probe microscopy of soft matter : fundamentals and practices. - T͡Sukruk, V. V. (Vladimir Vasilʹevich) (Wiley, 2011)
Well-structured and adopting a pedagogical approach, this self-contained monograph covers the fundamentals of scanning probe microscopy, showing how to use the techniques for investigating physical and chemical properties on the nanoscale and how they can be used for a widerange of soft materials. It concludes with a section on the latest techniques in nanomanipulation and patterning. This first book to focus on the applications is a must-have for both newcomers and established researchers using scanning probe microscopyin soft matter research. From the contents:>